Mechanism of differential enrichment of shale oils in the upper and lower members of the Lucaogou Formation in the Jimusaer Sag, Junggar Basin. (August 2022) - Liu, Shiju; Gao, Gang; Jun, Jin; Misch, David; Xinsong, Wu; Gang, Wenzhe; Wang, Ming; Baoli, Xiang; Wanyun, Ma
Abstract: Shale oil exploration and development have been conducted in the Permian Lucaogou Formation in the Jimusaer Sag, Junggar Basin. The upper (P2 l 2 ) and lower (P2 l 1 ) members of the Lucaogou Formation developed with sand layers, which are the shale oil development sections in the Lucaogou Formation. In order to clarify the enrichment law of shale oil for these members, the geological conditions of the P2 l 2 and P2 l 1 members were analyzed. The focus of this study were oil-bearing sandstone and mudstone samples from the Lucaogou Formation. These samples were studied by casting thin section observation, total organic carbon, pyrolysis, and gas chromatography–mass spectrometry. The results showed that the upper and lower members of the Lucaogou Formation are mainly characterized as interbedded source rock and reservoir. An oil-source correlation showed that the crude oil in the upper member mainly originated from its adjacent source rock from a deeper position through secondary migration. However, no evidence of secondary migration was observed in the crude oil in the lower member which mainly originated from the adjacent source rock. For the sandbodies in the upper member, when burial is shallower than peak oil generation, the physical properties of the middle part of the sandbody are better than the top and bottom. When burial is deeper than peak oil generation, relatively good physical properties developed in the sandstone in the vicinity the source rock. The lower member has less reservoir thickness, poorer lateral continuity and horizontal permeability than the upper member. The high-quality reservoirs are represented in a single sandbody in the lower member that is mainly developed in the middle part. After the crude oil was discharged from the source rock enters the sandbody, and long-distance lateral migration was restricted. Thus, crude oil in the lower member is enriched and accumulated in situ. Highlights: The characteristics of the source rocks and reservoir of the upper and lower members of the Lucaogou Formation are described. The oil-source correlation in the upper and lower reservoirs of the Lucaogou Formation have been discussed. The oil accumulation model of the upper and lower member of the Lucaogou Formation is established.